Effective components of teachers' professionalism in viewpoints of various stakeholders - Fatemeh Keshmiri; Sara Jambarsang; Amir Houshang Mehrparvar (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The teacher must conduct educational responsibilities in the best way by observing the ethical principles to meet students' educational needs. The aim of the study was to investigate the main factors of professionalism among faculty members from the viewpoints of various stakeholders including learners, peers, and educational officials, as well as the components were assessed from the viewpoints of the stakeholders. MATERIALS AND METHODS: This was a descriptive analytical study conducted in two phases. In the first phase, a questionnaire was developed and validated to assess the professional behavior of faculty members. In the second phase, the evaluation of the teachers' professional behavior was done from the viewpoint of various stakeholders, including learners, middle and senior education managers and peers. The participants were faculty members from 10 schools enrolled in the study by census (n = 427). To extract the factors that constitute professional behavior in faculty members, exploratory factor analysis was used. Data were summarized using descriptive indices (mean, standard deviation, and percent). Exploratory factor analysis (EFA) was used to extract the factors that constitute professional behavior in faculty members. Data was analyzed by using SPSS software (version 23.0). RESULTS: In the first phase, the questionnaire with 11 items was developed. The validity and reliability of the tool was confirmed. The mean (SD) of the faculty members' scores was 4.54(±0.34), with a minimum score of 2.33 and a maximum score of 5.00. The highest scores of faculty members were reported in the items of "altruism to colleagues and students" and the lowest scores were related to "feedback seeking and feedback acceptance". Professional behavior was categorized under two domains: accountability to professional duties and adherence to professional values. Fifty percent of the participants followed the adherence to professional values (P = 0.22), but less than 50% of the individuals followed the adherence to professional duties significantly (P = 0.002). CONCLUSION: The results of the present study showed that adherence to professional duties was low in faculty members. Assessment of individuals' adherence in these two domains showed that faculty members' compliance in the domain of accountability to professional duties was significantly lower.